KAJIAN STILISTIKA: ANALISIS MAKNA DIKSI DALAM PUISI "DI GURUN-GURUN PENGASINGAN" KARYA JABRA IBRAHIM JABRA - Yasmin Saffana Nuha (TEXTURA, 2021)
ABSTRACTThis research analyzes the meaning of diction in one of Jabra Ibrahim Jabra's literary works in the form of poetry, entitled "Di Gurun-Gurun Pengasingan". The theory used in this research is stylistic theory. Stylistic theory is a literary theory used to analyze aspects of language in a literary work, including diction or word choice. This research was written with a qualitative method. Qualitative method is a method used to analyze certain natural objects and the results of this research method emphasize more on the meaning of the object under study. The stylistic theory and qualitative methods used in this study aim to find out the meaning of the diction in the poem "Di Gurun-Gurun Pengasingan". The results of this study indicate that the diction in the poem by Jabra Ibrahim Jabra has an implied meaning about the state of Palestine before and after the attack from the Israeli army and that meaning is realized by natural dictions.Keywords: Stylistic Analysis, Poetry, Diction